Nutritional status and quality of life of candidates for heart transplantation - Chaves, Luana Najara Ferreira (2018)
Objective: To assess the nutritional status and quality of life of candidates for heart transplantation. Methods: Quantitative descriptive study of candiates for heart transplantation attending the outpatient clinic of a Heart Failure and Transplant Center (HFTC) in Fortaleza, Ceará, Brazil. Interviews, consultations and medical records were used to collect data on weight, height, Body mass index (BMI), arm circumference (AC), arm muscle circumference (AMC), triceps skinfold (TS) and clinical data on the underlying disease. Questionnaires addressing socioeconomic data, lifestyle and dietary frequency and the World Health Organization Quality of Life-WHOQOLBref were used. Descriptive statistics and absolute and relative frequencies were used. Continuous variables were tested using Pearson’s correlation coefficient. Results: Participants’ mean age was 50.64±12.45 years and 57% (n=27) were men. As for nutritional status, 47.22% (n=17) of the adults were overweight and 54.55% (n=6) of the older people were at normal weight. In addition, adults presented normal AC, AMC and TS, with 52.78% (n=19), 88.82% (n=32) and 36.11% (n=13), respectively. The older people also presented normal AC and AMC, both with 81.82% (n=9). Quality of life (QoL) was satisfactory (fair) according to the mean of the domains. Conclusion: The patients presented normal nutritional status and/or overweight and a quality of life ranging from fair to good. The variations in the NS and QoL depend on the life stage and on the social/family support they receive, which constitute positive determinants even in the presence of heart disease.